Internationalization Practices and Preparations: A Case of a State University in Central Luzon, Philippines - Rogayan Jr, Danilo V.; Mendoza, Ma. Shiela G. (Future Science / FSH-PH Publications, 2023)
In the era of internationalization, Philippine higher education institutions (HEIs) are compelled to continually refine their operations and governance to align with global standards. This descriptive cross-sectional survey research was conducted to assess the extent of practices and preparations for internationalization at a state university in Central Luzon, Philippines. The study engaged four administrators and 21 faculty members as respondents, collectively offering a perspective on the university's approach to internationalization. The study reveals that the university has initiated practices and preparations geared towards internationalization. Nonetheless, it is evident that there is room for further enhancement of its strategic directions and plans to more comprehensively integrate internationalization into its academic programs, policies, and administrative processes. This paradigm shift will require a measured, time-sensitive approach to ensure that the university meets its internationalization goals successfully. To expedite this process, the university administration could proactively take the lead in championing and facilitating internationalization efforts. This proactive leadership is pivotal in building a culture of global engagement, forging international partnerships, and positioning the university as a frontrunner in the international academic landscape. By doing so, the university can more effectively embrace the challenges and opportunities of internationalization in higher education.